Outcomes of Individualized Formative Assessments in a Pharmacy Skills Laboratory - Gums, Tyler Harris (Am J Pharm Educ, 2014)
Objective: To determine the effectiveness of an individualized teaching method in a pharmacy skills laboratory. Design: All third-year students enrolled in an Accreditation Council for Pharmacy Education (ACPE) accredited doctor of pharmacy program (n=150) received an individual formative assessment from clinical pharmacists on communication skills and clinical competency after the students counseled standardized mock glaucoma patients during a laboratory focused on alternative dosing formulations. Objective structured clinical examination (OSCE) scores for this station from the 2012 and 2013 classes were compared before and after the intervention. Assessment: Ophthalmic OSCE station scores were higher after the individual formative feedback intervention. Students in 2013 had a mean score of 83.2 ± 8.3% compared to a mean of 74.3 ± 12.9% in 2012 for this OSCE station. The percentage of students receiving an “A” on the OSCE station increased from 8.1% to 31.3% after the intervention. Conclusion: Individualized formative teaching methods benefited students in both their communication skills and clinical assessment. Future research should focus on wider implementation and overcoming obstacles, such as increased facilitator needs.